Obywatele . Citizens - Woldan, Pawel (Telewizia Polska, 1997)
Duration: 00:11:00 The movie is a sarcastic portrayal of rural community whose members show intense nostalgy toward the communist period with its mobilizational goals and bombastic life-style fuelled by intense propaganda. The director takes the slogans of the psot-communist present and confrunts these people with them. This can be considered a test for the deep structures of communist socialization in this community, which in itself could be taken as representative for similar other regions and groups in Poland.